INTENSI PEKERJA RUMAH TANGGA KORBAN PELECEHAN SEKSUAL UNTUK MELAPOR - Putriningsih, Nediyan; Stanislaus, Sugiyarta (Intuisi : Jurnal Psikologi Ilmiah, 2012)
Abstrak. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Unit analisisnya yaitu Intensi Pekerja Rumah Tangga Korban Pelecehan Seksual. Guna mendukung perolehan data yang mendalam digunakan pengambilan data melalui wawancara, observasi, dokumentasi, dan catatan lapangan kepada dua orang narasumber utama, dan empat orang narasumber sekunder penelitian.Hasil penelitian ini menunjukkan, bahwa intensi pekerja rumah tangga korban pelecehan seksual untuk melapor ke kepolisian (studi kasus pada pekerja rumah tangga yang masih di bawah umur sesuai dengan undang-undang no. l3 tahun 2003) dipengaruhi oleh beberapa faktor, yakni: bentuk dan dampak dari pelecehan seksual, intensitas pelecehan seksual yang terjadi, ketaatan akan agama, pengetahuan akan etika seksual dalam budaya jawa, faktor kepribadian, serta pengetahuan akan fungsi kepolisian Republik Indonesia. Adapun saran dari penelitian ini ialah pemerintah harus mempertegas kembali tentang larangan untuk memperkerjakan anak dibawah umur serta memberikan sanksi yang jelas bagi pelanggarnya, diharapkan LSM yang terkait dengan Pekerja Rumah Tangga lebih giat untuk membantu memerangi adanya pekerja yang masih dibawah umur dengan terus mengupayakan undang-undang yang dapat menaungi mereka, serta perlunya penggalian data yang lebih mendalam bagi peneliti selanjutnya guna mendapatkan informasi mengenai penyebab intensi Pekerja Rumah Tangga korban pelecehan seksual untuk melapor ke kepolislan. Kata kunci: intensi, pelecehan seksual, pekerja rumah tangga Abstract. Acts of sexual harassment today, has shown how vulnerable the women in his life when the subject of sexual dissatisfaction men. One of the jobs that are vulnerable to sexual abuse is a Domestic Workers, especially for domestic workers who are minors. Employment as domestic workers who are in the domestic sphere, often requiring them to be in the house for 24 hours, so that domestic workers are "isolated" from society. Under these conditions, and with other supporting factors such as economic factors, educational factors, age factors, as well as an inability to resist the employer caused the Domestic Workers are vulnerable to acts of sexual abuse committed by the employer. Sexual harassment is certainly related to intentions to report offenders to the police. Hence, through this research the researchers wanted to know what are the factors that led to the Domestic Workers have the intention to report the perpetrators of sexual abuse to the police. This study uses a qualitative case study approach. The unit of analysis is intention Domestic Workers Sexual Abuse Victims. In order to support the acquisition of the data used in-depth data collection through interviews, observation, documentation, and field notes to the two main speakers, resource persons and four secondary research.  The results of this study indicate, that the intentions of domestic abuse victims to report to police (case study on domestic Workers who are minors in accordance With the law No. l3 of 2003) is influenced by several factors, namely: the shape and impact of sexual harassment, the intensity of sexual abuse that occurred, the observance of religion, knowledge of sexual ethics in Javanese culture, personality factors, and knowledge of police functions of the Republic of Indonesia. The suggestion from this study is that the government should reinforce the back of the prohibition to employ minors as well as providing clear sanctions for violations, is expected to NGOs associated with more aggressive domestic Workers to help fight the Workers who are still minors to continue to pursue legislation which can be overshadowed them, and the need for a more in- depth data mining for further research in order to obtain information about the cause of the intentions of Domestic Workers of sexual abuse victims to report to police.